The effect of computer courses on developing teachers’ technological skills from viewpoint of teachers of Southern Jordan Valley schools - Al-Muradat, Osama Ahmed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to uncover the effect of computer courses on developing teachers’ technological skills, and in order to achieve the aim of the study, a descriptive analytical approach was used and a questionnaire was developed to collect data from the study sample, which included (333) teachers from the southern Jordan Valley schools, where (324) questionnaires were retrieved and valid for statistical analysis, with a rate of (97.3%) of the total distributed questionnaires. The results of the study showed that the degree to which teachers of Southern Jordan Valley schools possessed technological skills was of a moderate degree, and there is a statistically significant effect at the level of significance (α≤0.05) for computer courses with all its dimensions (training material, trainer, activities) in developing the skills of technological teachers. In light of the results obtained, the study recommended the necessity of increasing attention to training centers for computer courses in terms of providing them with adequate and modern technological equipment, and using qualified trainers who have extensive experience in the field of computers and technology.